Update and audit of the St George's classification algorithm of primary lymphatic anomalies: a clinical and molecular approach to diagnosis. Issue 10 (14th May 2020) - Gordon, Kristiana; Varney, Ruth; Keeley, Vaughan; Riches, Katie; Jeffery, Steve; Van Zanten, Malou; Mortimer, Peter; Ostergaard, Pia; Mansour, Sahar
Abstract : Primary lymphatic anomalies may present in a myriad of ways and are highly heterogenous. Careful consideration of the presentation can lead to an accurate clinical and/or molecular diagnosis which will assist with management. The most common presentation is lymphoedema, swelling resulting from failure of the peripheral lymphatic system. However, there may be internal lymphatic dysfunction, for example, chylous reflux, or lymphatic malformations, including the thorax or abdomen. A number of causal germline or postzygotic gene mutations have been discovered. Some through careful phenotyping and categorisation of the patients based on the St George's classification pathway/algorithm. The St George's classification algorithm is aimed at providing an accurate diagnosis for patients with lymphoedema based on age of onset, areas affected by swelling and associated clinical features. This has enabled the identification of new causative genes. This update brings the classification of primary lymphatic disorders in line with the International Society for the Study of Vascular Anomalies 2018 classification for vascular anomalies. The St George's algorithm considers combined vascular malformations and primary lymphatic anomalies. It divides the types of primary lymphatic anomalies into lymphatic malformations and primary lymphoedema. It further divides the primary lymphoedema into syndromic, generalised lymphatic dysplasia with internal/systemic involvement, congenital-onset lymphoedema and late-onset lymphoedema. An audit and update of the algorithm has revealed where new genes have been discovered and that a molecular diagnosis was possible in 26% of all patients overall and 41% of those tested.